Integrating space and time in visual search: how the preview benefit is modulated by stereoscopic depth. - Dent, K; Braithwaite, J; He, X; Humphreys, G (2012)
We examined visual search for letters that were distributed across both 3 dimensional space, and time. In Experiment 1, when participants had foreknowledge of the depth plane and time interval where targets could appear, search was more efficient if the items could be segmented either by depth or by time (with a 1000 ms preview), and there were increased benefits when the two cues (depth and time) were combined. In Experiments 2 and 3 the target depth plane was always unknown to the participant. In this case, depth cues alone did not facilitate search, though they continued to increase the preview benefit. In Experiment 4 new items in preview search could fall at the same depth as preview items or a new depth. There was a substantial cost to search if the target appeared at a previewed depth. Experiment 5 showed that this cost remained even when participants knew the target would appear at the old depth on 75% of trials. The results indicate that spatial (depth) and temporal cues combine to enhance visual segmentation and selection, and this is accomplished by inhibition of distractors in irrelevant depth planes.